Chemical disguise of myrmecophilous cockroaches and its implications for understanding nestmate recognition mechanisms in leaf-cutting ants. Issue 1 (December 2016) - Nehring, Volker; Dani, Francesca; Calamai, Luca; Turillazzi, Stefano; Bohn, Horst; Klass, Klaus-Dieter; d'Ettorre, Patrizia
Abstract Background Cockroaches of the genusAttaphila regularly occur in leaf-cutting ant colonies. The ants farm a fungus that the cockroaches also appear to feed on. Cockroaches disperse between colonies horizontally (via foraging trails) and vertically (attached to queens on their mating flights). We analysed the chemical strategies used by the cockroaches to integrate into colonies ofAtta colombica andAcromyrmex octospinosus. Analysing cockroaches from nests of two host species further allowed us to test the hypothesis that nestmate recognition is based on an asymmetric mechanism. Specifically, we test the U-present nestmate recognition model, which assumes that detection of undesirable cues (non-nestmate specific substances) leads to strong rejection of the cue-bearers, while absence of desirable cues (nestmate-specific substances) does not necessarily trigger aggression. Results We found that nests ofAtta andAcromyrmex contained cockroaches of two different and not yet describedAttaphila species. The cockroaches share the cuticular chemical substances of their specific host species and copy their host nest's colony-specific cuticular profile. Indeed, the cockroaches are accepted by nestmate but attacked by non-nestmate ant workers. Cockroaches fromAcromyrmex colonies bear a lower concentration of cuticular substances and are less likely to be attacked by non-nestmate ants than cockroaches fromAtta colonies. Conclusions Nest-specific recognition ofAttaphila cockroaches by host workers in combination with nest-specific cuticular chemical profiles suggest that the cockroaches mimic their host's recognition labels, either by synthesizing nest-specific substances or by substance transfer from ants. Our finding that the cockroach species with lower concentration of cuticular substances receives less aggression by both host species fully supports the U-present nestmate recognition model. Leaf-cutting ant nestmate recognition is thus asymmetric, responding more strongly to differences than to similarities.